2013
DOI: 10.1111/jgs.12445
|View full text |Cite
|
Sign up to set email alerts
|

Mild Chronic Kidney Disease Associated with Greater Risk of Arterial Stiffness in Elderly Adults

Abstract: Mild and moderate CKD increased the risk of greater arterial stiffness in elderly adults. Age, prediabetes mellitus, diabetes mellitus, prehypertension, and hypertension were also important correlates of increased arterial stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
1
7
0
3
Order By: Relevance
“…It has been speculated that urinary NGAL in this population may reflect early chronic tubular damage that may be indicative of an increased mortality risk. Many previous studies have found that baPWV is related to both eGFR and chronic kidney disease (CKD) . The present study (Figure ) found that the mean baPWV differed significantly between eGFR tertiles in both the low and high urinary NAG groups.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…It has been speculated that urinary NGAL in this population may reflect early chronic tubular damage that may be indicative of an increased mortality risk. Many previous studies have found that baPWV is related to both eGFR and chronic kidney disease (CKD) . The present study (Figure ) found that the mean baPWV differed significantly between eGFR tertiles in both the low and high urinary NAG groups.…”
Section: Discussionsupporting
confidence: 51%
“…Age, hypertension, BP, and the white blood cell count have also been reported to be important correlates of greater baPWV . Heart rate and BMI have also been associated with baPWV .…”
Section: Discussionmentioning
confidence: 98%
“…A series of studies reported that there was a linear association for renal impairment and arterial stiffness [21–25]. However, most of them did not address nonlinearity, and did not perform the subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms including those related to CKD have been suggested to be involved in accelerated vessel stiffening (3,8,(10)(11)(12)(13). Identified factors associated with increasing PWV in non-dialysed CKD patients are age, black ethnicity, male gender, hypertension and diabetes mellitus (13)(14)(15)(16). Evidence indicates that stiffening of the aorta may decrease in patients on maintenance dialysis (17).…”
Section: Introductionmentioning
confidence: 99%